Pathological findings of an eye anomaly in Randall's threadfin bream Nemipterus randalli Russell, 1986 from the Mediterranean Sea (Antalya Gulf-Türkiye) - Şükrü GÜNGÖR; Özlem ÖZMEN; Deniz İNNAL (Cluj Veterinary Journal)
Genetic, environmental and nutritional conditions seriously affect the health of natural fish stocks. In addition, increasing human pressure on aquatic systems in recent years is threatening fish populations. Under the influence of increasing environmental pressures and other factors, different types of abnormalities are observed in fish. Among these, morphological abnormalities, pigmentation abnormalities, eye abnormalities, visceral abnormalities and reproductive abnormalities are commonly observed. There is limited information on eye abnormalities in Mediterranean fish species. In the present study, the body abnormality observed in a trawl-caught specimen of Randall's threadfin bream, in which the eyes were missing, and its causes are reported and the pathological findings discussed.